The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.mayocpiqo.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Exertional Chest Pain in a Marathon Runner: Exercise-induced, Painful, Left Bundle Branch Block Syndrome Treated With His-Bundle Pacing

Abstract: A 49-year-old woman presented with exercise-induced chest discomfort during long-distance running that was occasionally present during rest. Significant coronary artery disease was excluded and a diagnosis of “painful left bundle branch block (LBBB) syndrome” was made after correlation of LBBB aberrancy with symptoms during Holter monitoring. The patient underwent confirmatory testing consisting of rapid atrial pacing below and above 130 beats per minute, the rate cut-off for LBBB manifestation. His bundle pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…We noticed consistent response with complete resolution of chest pain in cases treated by His-bundle pacing in five reported cases in the literature. [1][2][3][4][5] Reporting this case will increase our awareness of this clinical entity and enhance our evidence about His-bundle pacing as an effective treatment modality in this condition.…”
Section: Introductionmentioning
confidence: 80%
“…We noticed consistent response with complete resolution of chest pain in cases treated by His-bundle pacing in five reported cases in the literature. [1][2][3][4][5] Reporting this case will increase our awareness of this clinical entity and enhance our evidence about His-bundle pacing as an effective treatment modality in this condition.…”
Section: Introductionmentioning
confidence: 80%
“…13 Recent studies have shown that His Bundle Pacing (HBP) induces significant QRS narrowing in most patients with LBBB and even normalization in patients with shorter baseline QRS duration 14 supporting the theory of functional longitudinal dissociation in the His Bundle. HBP has also been shown to effectively alleviate symptoms in exerciseinduced painful LBBB 15 which suggests a pathology in the His bundle with altered refractoriness in a rate dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…LBBB results from a degeneration of the conduction system or is a reflection of myocardial pathology. Complete LBBB is characterized by a QRS duration of 120 ms or more, predominantly upright complexes with broad-slurred R waves in leads I and V6, a QS or rS complex in lead V1, and a monophasic R wave in leads I, V5, and V6 [ 2 ]. The main causes of new onset LBBB include coronary artery disease, cardiomyopathies, and hypertension [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of the heart rate is considered the most common cause of ILBBB, which is usually caused by phase 3 block or tachycardia-dependent block when a stimulus reaches the tissues that are still in the refractory period [ 3 , 4 ]. Exercise-induced ILBBB is a rare phenomenon that occurs in 0.1% to 1.1% of patients undergoing diagnostic EST [ 2 ]. It has been reported that the onset of ILBBB at a heart rate greater than 125 bpm is highly consistent with normal coronary arteries, but it has been noticed to occur at a slower rate of <105 bpm, like the presentation of our patient [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation